Signatures of equatorial plasma bubbles in VHF satellite scintillations and equatorial ionograms. Issue 2 (6th March 2013) - McNamara, L. F.; Caton, R. G.; Parris, R. T.; Pedersen, T. R.; Thompson, D. C.; Wiens, K. C.; Groves, K. M.
<x xml:space="preserve">Abstract</x> Since their discovery in the 1970s, equatorial plasma bubbles (EPBs) have been invoked to explain the propagation of VHF signals on trans‐equatorial circuits at night, and blamed for highly detrimental scintillation of VHF and GHz trans‐ionospheric communications signals in equatorial regions. Over the last four decades, the properties of EPBs have been deduced by multiple techniques such as incoherent scatter radar, 630 nm airglow, depletions in GPS total electron content observations, VHF and GHz scintillations, and HF observations by ionosondes. The initiation and evolution of EPBs have by now been successfully modeled and a good understanding developed of the underlying physics. However, different communities tend to concentrate on a single observing technique, without regard to whether the different techniques provide a consistent physical picture. In contrast, this paper discusses two very different types of observations made on a night‐by‐night basis during the COPEX campaign of late 2002 in Brazil, namely, VHF scintillations and ionograms, and shows that the two methods of observation can provide a consistent interpretation of the properties of EPBs. For example, an EPB seen as an eastward drifting scintillation event can also be seen as an extra ionogram reflection trace that moves closer to and then away from the ionosonde site. The scintillations are attributed to strong gradients across the walls of an EPB, whereas the extra ionogram traces are attributed to oblique reflection of the ionosonde signals from the walls of the EPB.